Entrepreneurship performance indicators for employer enterprises in Portugal - Sarmento, Elsa (2010)
This study provides a description of active employer enterprises and enterprise creation dynamics in Portugal, using an entrepreneurship dataset conceived from Quadros de Pessoal based on the Eurostat/OECD methodology “Manual on Business Demography Statistics”, for the period 1987 to 2007. Using this unique matched employer-employee micro dataset, we discuss the prevalence of some of the main stylised facts of firm creation and firm size distribution. The main contribution of this analysis is to provide detailed disaggregated evidence of the performance of employer enterprises by firm dimension, region and main economic sectors over a period of 20 years. When relevant, we resort to international data for comparison.